Biosorption of metal elements by exopolymer nanofibrils excreted from Leptothrix cells. (1st October 2017) - Kunoh, Tatsuki; Nakanishi, Makoto; Kusano, Yoshihiro; Itadani, Atsushi; Ando, Kota; Matsumoto, Syuji; Tamura, Katsunori; Kunoh, Hitoshi; Takada, Jun
Abstract: Leptothrix species, aquatic Fe-oxidizing bacteria, excrete nano-scaled exopolymer fibrils. Once excreted, the fibrils weave together and coalesce to form extracellular, microtubular, immature sheaths encasing catenulate cells of Leptothrix . The immature sheaths, composed of aggregated nanofibrils with a homogeneous-looking matrix, attract and bind aqueous-phase inorganics, especially Fe, P, and Si, to form seemingly solid, mature sheaths of a hybrid organic–inorganic nature. To verify our assumption that the organic skeleton of the sheaths might sorb a broad range of other metallic and nonmetallic elements, we examined the sorption potential of chemically and enzymatically prepared protein-free organic sheath remnants for 47 available elements. The sheath remnants were found by XRF to sorb each of the 47 elements, although their sorption degree varied among the elements: >35% atomic percentages for Ti, Y, Zr, Ru, Rh, Ag, and Au. Electron microscopy, energy dispersive x-ray spectroscopy, electron and x-ray diffractions, and Fourier transform infrared spectroscopy analyses of sheath remnants that had sorbed Ag, Cu, and Pt revealed that (i) the sheath remnants comprised a 5–10 nm thick aggregation of fibrils, (ii) the test elements were distributed almost homogeneously throughout the fibrillar aggregate, (iii) the nanofibril matrix sorbing the elements was nearly amorphous, and (iv) these elements plausibly were bound to the matrix by ionic binding, especially via OH. The present results show that the constitutive protein-free exopolymer nanofibrils of the sheaths can contribute to creating novel filtering materials for recovering and recycling useful and/or hazardous elements from the environment. Graphical abstract: Highlights: Biosorption of 47 elements by exopolymer nanofibrils excreted from Leptothrix cells are tested. The sorbed elements distribute almost homogeneously throughout the fibrillar aggregate. The nanofibril matrix sorbing the elements is nearly amorphous. The sorbed elements plausibly are bound to the matrix by ionic binding, especially via OH.